Energy Efficiency Management and Greenhouse Gas Emissions in Industrialized Countries: A panel CS - ARDL Approach - Toumi, Bilal; Toumi, Mohamed; Satour, Rachid; Kifaifi, Houssam (Journal of Ecohumanism, 2025)
This study investigates the relationship between energy efficiency improvements and greenhouse gas emissions in 16 industrialized countries over the period 1980–2023. Employing the Cross-Sectional Autoregressive Distributed Lag (CS-ARDL) model, which accounts for cross-sectional dependence and slope heterogeneity, the analysis reveals that energy efficiency improvements-proxied by energy intensity-are more effective in mitigating emissions than renewable energy deployment. Specifically, a 1% increase in energy intensity raises emissions by 0.1883% in the long run, while a 1% increase in renewable energy consumption reduces emissions by 0.0570%. These findings highlight the critical importance of prioritizing energy efficiency measures alongside renewable energy investments to achieve meaningful emission reductions in industrialized economies.